Possibilities of roentgenendovascular interventions in massive arosive hemorrhage on background of acute destructive pancreatitis - V. V. Grubnik; O. M. Zahorodniuk; Ye. A. Koichev; M. M. Chernov (Клінічна хірургія, 2020)
Objective. To estimate the efficacy of roentgenendovascular interventions in massive arosive hemorrhage in patients with an acute destructive pancreatitis.